The characteristics of tobacco, alcohol and substance use among the children who apply to protection centers in İstanbul - Ögel, Kültegin; Aksoy, Alper (Journal of Dependence, 2008)
Objective: Despite the fact that it’s seen that tobacco, alcohol and substance use is widespread among children who apply to protection centers, knowledge about prevalence and characteristics of usage is very rare. In current research it was aimed to investigate the prevalence, onset and characteristics of substance use among the children who use substances and apply to protection centers in İstanbul. Method: One hundred and ninety four children and adolescents who were under age of 21 and who stayed in protection centers in İstanbul between the years 2002 and 2003 were included in the study. Those who haven’t spent most of the nights with their parents and stayed in the streets at least for the last month were defined as street children. A questionnaire that was developed by the authors and SCID interview form for the DSM IV was used. Results: %78 of children who were included in the study was found to use substances apart from tobacco and alcohol. The most widely used substances among males were found to be tobacco, inhalants, alcohol and adhesives respectively. Also, the most widely used substances among females were tobacco, alcohol, marijuana and adhesives respectively. The risk for males to start substance use immediately as they start to live in the street was three times higher and the risk of regular use was ten times higher than females. Discussion: The prevalence of substance use and addiction among the children living on the street is much higher than their peers. In relation with the findings, the number of prevention and treatment programs for the children living on the streets should be improved.